2015
DOI: 10.1101/cshperspect.a005959
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Networks that Regulate Cell Migration

Abstract: SUMMARYStimuli that promote cell migration, such as chemokines, cytokines, and growth factors in metazoans and cyclic AMP in Dictyostelium, activate signaling pathways that control organization of the actin cytoskeleton and adhesion complexes. The Rho-family GTPases are a key convergence point of these pathways. Their effectors include actin regulators such as formins, members of the WASP/WAVE family and the Arp2/3 complex, and the myosin II motor protein.Pathways that link to the Rho GTPases include Ras GTPas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
231
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(239 citation statements)
references
References 175 publications
(188 reference statements)
6
231
0
2
Order By: Relevance
“…Due to a mutation of the RasGAP neurofibromin NF1, in axenic Dictyostelium strains, excessive Ras signaling appears to bypass the requirement for fAR1-receptor activation and makes macropinocytosis constitutive, allowing the cells to grow efficiently in liquid medium (10). The links between PIP 3 and the cytoskeleton are not yet fully resolved, but several downstream effectors of this phosphoinositide, including RacGEFs and Akt, have been proposed to lead to activation of Arp2/3 complex-mediated actin assembly (63,64). Previous work demonstrated that mutants lacking PI3Ks and the small GTPases RasG and RasS display a significantly decreased large-scale endocytosis, thus supporting the view that these proteins operate in a common signaling pathway (15,34).…”
Section: Resultsmentioning
confidence: 99%
“…Due to a mutation of the RasGAP neurofibromin NF1, in axenic Dictyostelium strains, excessive Ras signaling appears to bypass the requirement for fAR1-receptor activation and makes macropinocytosis constitutive, allowing the cells to grow efficiently in liquid medium (10). The links between PIP 3 and the cytoskeleton are not yet fully resolved, but several downstream effectors of this phosphoinositide, including RacGEFs and Akt, have been proposed to lead to activation of Arp2/3 complex-mediated actin assembly (63,64). Previous work demonstrated that mutants lacking PI3Ks and the small GTPases RasG and RasS display a significantly decreased large-scale endocytosis, thus supporting the view that these proteins operate in a common signaling pathway (15,34).…”
Section: Resultsmentioning
confidence: 99%
“…Cortical actin, approximately ~50-200-nm thick, is anchored underlying the inner face of the plasma membrane and provides a contractile force in the cortex with the presence of myosin in the network [35,36]. The cell cortex plays a critical role in cell shape changes during movement [27,37], which has been shown to stiffen as cells deform and aid the stability of shape changes [38], suggesting that the polymerization of cortical actin favors cell deformation during migration.…”
Section: / 28mentioning
confidence: 98%
“…PAK2 and ROCK I are serine-threonine kinase effectors of the Rho GTPase family (Rac1, Cdc42, and Rho) that regulate actin polymerization and actin-myosin contractility. Upon caspase cleavage, their kinase activity becomes independent of the GTPases, thus inducing an aberrant reorganization of the actin cytoskeleton and the characteristic membrane blebbing observed in apoptotic cells (Rudel and Bokoch 1997;Coleman et al 2001;Sebbagh et al 2001) (for more details on cytoskeleton-modulating proteins, see Devreotes and Horwitz 2014).…”
Section: Caspase Activation Function and Regulationmentioning
confidence: 99%